Imagens educam: lições de modernidade na imprensa ilustrada paulista e carioca na década de 1920 - Miyoshi, Simone Cléa dos Santos (2020)
This study had as its main objective to search in the illustrated magazines of the 1920s, the image representation of the ideals of modernity and civilization, through illustrations, photographs, advertisements, among others. The Fon-Fon, Grimace, The Cicada, Modern Life, The Mallet and Cinearte magazines profiled the universe of sources studied. It was based on the thesis that the image contents linked in these journals educated looks, shaped behaviors, influenced individual and collective identities, and finally formed subjects and citizens. The research, therefore, proposed a look at the visual culture of an era relating it to its potential educator, through different instruments, carriers and supports, where they place images and their languages, as well as their narratives. Thus, we sought to offer a look at the History of Education about the illustrated press of the time, seeking to build a non-formal pedagogical scope, examining the visuality of these supports and building possible educational paths parallel to institutionalized education. In the light of the authors of the History of Education, History of Culture and Art, it was possible to build analyzes about iconic, iconographic, illustrative or constructed images, allowing to locate the visual lessons and their narratives, recognizing multiple and diverse voices that envisioned and sought to forge. a society.